The politics of unsafe abortion in Burkina Faso: The interface of local norms and global public health practice - Storeng, Katerini T. (Glob Public Health, 2014)
In Burkina Faso, abortion is legally restricted and socially stigmatised, but also frequent. Unsafe abortions represent a significant public health challenge, contributing to the country's very high maternal mortality ratio. Inspired by an internationally disseminated public health framing of unsafe abortion, the country's main policy response has been to provide post-abortion care (PAC) to avert deaths from abortion complications. Drawing on ethnographic research, this article describes how Burkina Faso's PAC policy emerged at the interface of political and moral negotiations between public health professionals, national bureaucrats and international agencies and NGOs. Burkinabè decision-makers and doctors, who are often hostile to induced abortion, have been convinced that PAC is ‘life-saving care’ which should be delivered for ethical medical reasons. Moreover, by supporting PAC they not only demonstrate compliance with international standards but also, importantly, do not have to contend with any change in abortion legislation, which they oppose. Rights-based international NGOs, in turn, tactically focus on PAC as a ‘first step’ towards their broader institutional objective to secure safe abortion and abortion rights. Such negotiations between national and international actors result in widespread support for PAC but stifled debate about further legalisation of abortion.